2015
DOI: 10.1039/c5an01300c
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-catalyzed uranine reduction for signal amplification in fluorescent assays for melamine and aflatoxin B1

Abstract: A multifunctional fluorescence platform has been constructed based on gold nanoparticle (AuNP)-catalyzed uranine reduction. The catalytic reduction of uranine was conducted in aqueous solution using AuNPs as nanocatalyst and sodium borohydride as reducing reagent, which was monitored by fluorescence and UV-vis spectroscopy. The reaction rate was highly dependent on the concentration, size and dispersion state of AuNPs. When AuNPs aggregated, their catalytic ability decreased, and thereby a label-free fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Knopp's group also designed a magnetic bead-based fluorescent immunoassay for AFB1 using AuNP-catalyzed uranine reduction for signal amplification. 46 Due to the high catalytic activity of AuNP toward uranine, the developed fluorescence system exhibited a high sensitivity for AFB1 with a detection limit of 17.1 pg mL −1…”
Section: ■ Typical Optical Sensing Strategiesmentioning
confidence: 99%
“…Knopp's group also designed a magnetic bead-based fluorescent immunoassay for AFB1 using AuNP-catalyzed uranine reduction for signal amplification. 46 Due to the high catalytic activity of AuNP toward uranine, the developed fluorescence system exhibited a high sensitivity for AFB1 with a detection limit of 17.1 pg mL −1…”
Section: ■ Typical Optical Sensing Strategiesmentioning
confidence: 99%
“…Therefore, once the total amount of gold present in the solution reacts with the sodium borohydride, 4-aminophenol will be formed. 38,40,60,61 However, in the presence of Au nanocatalyst, the complete reduction of 4-nitrophenolate to 4-aminophenol by NaBH 4 was observed within a few minutes, B4 minutes maximum, (Fig. 12B) revealing that the resultant Au nanocatalyst indeed possessed excellent catalytic activity for the reduction of 4-nitrophenol.…”
Section: Catalytic Activity Of Au Nanowires Vs Nanoparticlesmentioning
confidence: 96%
“…The present work could serve the purpose of gaining a better understanding on how different parameters affect the formation of gold nanowires and their potential application in catalysis of the reduction of nitro-aromatics, since the reduction of organic compounds like 4-nitrophenol has been used for the detection of different proteins; however, this catalytic reduction is only limited to several colored substances, including methyl orange, 4-nitrophenol and methylene blue. [36][37][38][39][40] In our earlier work, 20 we reported that curcumin could help in the formation of Au nanorods through pre-reduction and it enhances Au nanorod formation prepared from CTAB capped over citrate capped Au seeds. In the available literature, the role of OH À in dictating the size and shape of Au nanowires is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…This method was also legalised as an effective procedure for melamine detection, but still much focus is required to improve its applicability and detection limits. Subsequently, the catalytic property of antibody conjugated Au NPs was exploited towards melamine determination by Knopp's group [150]. Surface-assisted laser desorption/ionization mass spectrometry (SALDI-MS) was engaged in the quantification of melamine in infant formula and grain powder by Hsieh and co-workers [164].…”
Section: Nanoparticles In Melamine Quantificationmentioning
confidence: 99%